Welcoming Finitude : Toward a Phenomenology of Orthodox Liturgy - Gschwandtner, Christina M., 1974- (Book collections on Project MUSE., 2019)
What does it mean to experience and engage in religious ritual? How does liturgy structure time and space? How do our bodies move within liturgy, and what impact does it have on our senses? How does the experience of ritual affect us and shape our emotions or dispositions? How is liturgy experienced as a communal event, and how does it form the identity of those who participate in it? Welcoming Finitude explores these broader questions about religious experience by focusing on the manifestation of liturgical experience in the Eastern Christian tradition. Drawing on the methodological tools of contemporary phenomenology and on insights from liturgical theology, the book constitutes a philosophical exploration of Orthodox liturgical experience.